Aiming towards hepatitis C virus elimination in Greece - Papatheodoridis, G. V.; Goulis, J.; Sypsa, V; Lionis, C.; Manolakopoulos, S.; Elefsiniotis, I.; Anagnostou, O.; Tsoulas, C.; Hatzakis, A; Dalekos, Gn (Ann Gastroenterol, 2019)
There are estimated to be 74,000-134,000 patients living with chronic hepatitis C in Greece, but only 20-30% of them are aware of their disease status. In July 2017, the Hellenic National Plan for Hepatitis C was announced in alignment with the World Health Organization goals for the eradication of hepatitis C virus (HCV) by the year 2030. This article discusses the epidemiology and current treatment of chronic hepatitis C in Greece. Additionally the authors propose actions on how to bring back to care diagnosed patients lost to follow up, optimize access to care for HCV-infected people who inject drugs, and increase HCV screening in the general population. The medical community in Greece can play a pivotal role in the implementation of the HCV National Plan and in the efforts to reach the goal of HCV elimination.